Efektifitas Pelatihan Kader Kesehatan dalam Penanganan Tuberkulosis di Wilayah Binaan - Elman Boy (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2015)
Background: Medan is an area with the largest TB patients in the North Sumatra Province. Since 2014, Medan Denai Distric is a target area of Medical Faculty of University Muhammadiyah North Sumatra (FM UMSU). One of the implemented program is  formulating a Community Forum on TB Care. The objective of this study is to find out the effectiveness of TB management training by improving the knowledge of health cadres. Method: This was a one-group pre test-and post-test design. Participants of the research were all the TB care Forum members that was selected by inclusive criterias. Data collection was conducted by using quesionnaires of knowledge. Data analysis used Wilcoxon test with significancy level = 0,05.Results: The cadres knowledge significantly rise after the TB management training.Conclusion: TB management training for health cadre was effective in improving knowledge of health cadre.